Optimization The Use of Production Factors And Rice Farming Income - Imran, Supriyo; Salim, Sri Verawati; Adam, Echan (Jambura Agribusiness Journal, 2023)
This study aimed to analyze lowland rice farming income and analyze the optimization of the use of production factors to achieve lowland rice farming efficiency in Telaga district, Gorontalo regency. This study was conducted from September to October 2021 by survey and interview, while the sampling used a simple random method. The data sources were both primary and secondary in type, while the data analysis used to examine the rice farming income used qualitative descriptive analysis. Further, the means to examine the optimization level of the production factor usage employed Cobb-Douglas analysis and Product Marginal Value. The findings showed the income average for a growing season reached Rp. 37.217.960 ha./GS., while the analysis results revealed the Revenue of Cost Ratio for farming achieved 2.14. Hence, the area is deemed feasible. Land area (X1), Seeds (X2), Fertilizer (X3), Pesticides (X4), and Labor (X5) had simultaneous effects on the income, but partially only fertilizer (X3) variable did not effect on the income. The use of production factors of land area, pesticides, and labor was not optimal because the optimization value obtained NMPxi 1, which means the need for reuse. Meanwhile, the use of seeds and urea fertilizer was not optimal yet because the optimization value obtained NMPxi 1, which means its usage needs improving to provide optimal interest for farmers at the research site.